(untitled) (International journal of artificial intelligence, 2025)
This study explores the linguocultural nature of stylistic synonyms and their role in representing national mentality and cultural identity in language. It focuses on how stylistic variations within synonymic groups express emotional, aesthetic, and social meanings. The paper highlights the connection between language and culture, showing that synonymic diversity is an indicator of a nation's worldview, traditions, and communicative norms.